x^y乘(2xy-3xy^2)=___________________=________________
2个回答
x^y*(2xy-3xy^2)
=2x^(y+1)y-3x^(y+1)y^2
=x^(y+1)y(2-3y)
相关问题
(3xy^2)^3乘[xy(2x-y)-2x(xy-y^2)].其中x=2 y=1/2
xy²=2,求代数式xy²乘(-x²y²)乘(1/2xy³)²
1、(-2x²)²×(-3x)³ 2、-10xy乘(-2²y-3xy²
y²分之(x²-2xy+y²)除以xy分之(y²-xy)乘xy²,其中x=4,y=3.
计算:-3/4(-2x^2y)^2乘以9(-1/3xy)-(-xy)^3乘以(-x^2)
[6xy^2乘(-2xy)^2-24x^5y^6除(-2xy)^2]除(-3xy^2)^2,其中x=2,y=2003
4x^2y乘(-xy^2)^3
计算 1.(-3xy)乘以y²-(-2xy²)²+(-2x)²乘以(-y)的四次
3xy²-[xy-2(xy-3/2x²y)+3xy²]+3xy²,其中x=3,y
【xy(x²-3y)+3xy²】(-2xy)+x³y²(2x-y)